Insights on the marine microbial nitrogen cycle from isotopic approaches to nitrification - Casciotti, Karen L.; Buchwald, Carolyn (Frontiers in Microbiology, 2012)
The microbial nitrogen (N) cycle involves a variety of redox processes that control the availability and speciation of N in the environment and are involved with the production of nitrous oxide (N2O), a climatically important greenhouse gas. Isotopic measurements of ammonium (NH4+), nitrite (NO2-), nitrate (NO3-), and N2O can now be used to track the cycling of these compounds and to infer their sources and sinks, which has lead to new and exciting discoveries. For example, dual isotope measurements of NO3- and NO2- have shown that there is NO3- regeneration in the ocean’s euphotic zone, as well as in and around oxygen deficient zones, indicating that nitrification may play more roles in the ocean’s N cycle than generally thought. Likewise, the inverse isotope effect associated with NO2- oxidation yields unique information about the role of this process in NO2- cycling in the primary and secondary NO2- maxima. Finally, isotopic measurements of N2O in the ocean are indicative of an important role for nitrification in its production. These interpretations rely on knowledge of the isotope effects for the underlying microbial processes, in particular ammonia oxidation and nitrite oxidation. Here we review the isotope effects involved with the nitrification process, the insights provided by this information, and provide a prospectus for future work in this area.